Social Resilience and Ecological Repercussions in Tere Liye’s Si Anak Pemberani - Anggraeni, Natalia Desy; Darni, Darni; Ahmadi, Anas; Subandyah, Heny (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to identify and explain the forms of social resilience and ecological repercussions presented in the novel Si Anak Pemberani by Tere Liye. The research uses a qualitative approach. The novel is analyzed in depth to identify representations of community resilience and the ecological consequences depicted by the author. The study finds that social resilience in the novel is reflected through the main character’s personal courage and the community’s solidarity in facing external threats. The characters maintain moral integrity and a spirit of mutual cooperation despite pressure, indicating a high level of social toughness. On the other hand, ecological repercussions are portrayed through the negative impacts of greed on nature, such as threats to the sustainability of the land, rivers, and forests in the village due to resource exploitation. The novel clearly illustrates how environmental destruction can backfire on society, serving as a warning about the consequences of excessive exploitation of nature. Si Anak Pemberani successfully depicts the community’s social resilience in defending truth and environmental preservation, while also emphasizing the ecological consequences of exploitative actions. The novel conveys the message that strong social solidarity and environmental awareness are key to confronting both social and ecological threats.